Variation Of Word Usage In Arabic Media: A Study On Selected Arabic Newspapers - Zainur Rijal Abdul Razak (USIM Press, 2024)
The main idea behind practising Modern Standard Arabic (MSA) is to standardise the use of the Arabic language in all Arab countries, especially in official communication, be it written or spoken. This is due to their belief that language is one of the important elements contributing to their unity and sense of brotherhood as they are separated by different legitimate territories. This effort has more or less succeeded in uniting them in certain aspects. In reality, however, the writer has found that the practice has yet to ensure the standardisation of the Arabic language, particularly in terms of word usage style among countries. Taking news articles as data, this paper aims to highlight the differences that occur in word usage in seven Arabic newspapers from different countries, with a corpus of around 85,000 words from the World Affairs section. The analysis also includes articles published in two Arabic newspapers from non-Arab countries in order to relate to the role of geography in creating word usage style in publishing. The Wordsmith 5.0 computer programme was applied to the corpus by extracting all words into frequency lists and concordance. The results show that the Arabic newspapers contributed greatly to the creation of word usage variations, specifically in terms of spelling, loan word acceptance, verb transitivity to particle, phrase combination and plural formation.